Measurement of Fetomaternal Outcome in Pregnant Patients with Sepsis: Fetomaternal Outcome with Sepsis in Pregnancy - Huma, Zill E; Jabeen, Asma; Jan, Sadiq; Afzal, Madiha; Aziz, Uzma; Salman, Nayla (Pakistan Journal of Health Sciences, 2024)
Sepsis during pregnancy is a severe condition associated with significant maternal and fetal morbidity and mortality. It necessitates early identification and intervention to mitigate adverse outcomes. Objectives: The study was aimed to evaluate and compare feto-maternal outcomes in pregnant patients with sepsis versus those without sepsis. Methods: This comparative cross-sectional study was conducted at Social Security Teaching Hospital, Lahore, from July 2023 to January 2024. A total of 240 pregnant women were included, with 120 diagnosed with sepsis and 120 without sepsis (control group). Obstetrically modified qSOFA and SOFA scores, were used for sepsis diagnosis. Data on vital signs, laboratory investigations, and fetal monitoring were collected and analyzed using SPSS version 24.0. Multivariate analysis was employed to adjust for potential confounders, and p-values of ≤ 0.05 were considered statistically significant. Results: The sepsis group exhibited significantly worse outcomes compared to the control group. The mean age was 27.8 ± 9.4 years, and mean Body mass index (BMI) was 25.3 ± 5.6. Maternal outcomes included 8.3 % oligohydramnios, 46.67 % cesarean sections for non-reassuring fetal profiles, and 15 % preterm premature rupture of membranes. Maternal Intensive Care Unit ICU admission was necessary for 8.3 % of patients, with a maternal mortality rate of 1.67 %. Fetal outcomes included 5 % intrauterine fetal growth restriction, 28.33 % small for gestational age, 3.3 % stillbirth, and 53.33 % neonatal ICU admissions. Conclusion: Sepsis in pregnancy significantly increases the risk of adverse feto-maternal outcomes, including preterm birth, fetal distress, intrauterine growth restriction, and neonatal complications. Early detection and aggressive management are crucial to improving outcomes.